A case study on the physical environment of special education learning and play center for children ages 3-12 years old - Reyes, Mary Grace Hapin
In the field of Interior Design, space planning of the physical environment can positively or negatively affect children's learning. The main objective of the study is to propose space planning solutions for a particular special education learning and play center which caters to the needs of special children with different types of disabilities such as, ADHD (Attention Deficit Hyperactive Disorder), Autism, Cerebral palsy, Down syndrome and Mental retardation ages three to twelve years old. The conceptual framework of the study integrates philosophy, curriculum and children's needs as independent variables for optimum space to a special education learning and play center. The data were gathered through questionnaires, interviews and observations of an actual special education learning and play center. Results were analyzed by assessing the center's capacity to provide all the children's needs and relating them to the factors of the physical environment with emphasis on safety and independent access. Results showed that therapists and teachers prefer a special education learning and play center that support their goal in education children with special needs. However, some philosophy and curriculum indicate that the center should focus on the physical environment and planning considerations namely, accessibility, hazard free, as well as using materials appropriate for children with special needs. The study suggests that the most appropriate setting for a special education learning and play center that can positively affect the children is having careful arrangement of space that can promote physical, social and emotional development. In proposing effective space planning solutions for special education learning and play center, design standards are not enough. It is important to consider philosophy, curriculum and needs assessment of the children and their disabilities.